Analysis of the concordance between the estimated values of creatinine clearance using the Cockcroft-Gault equation and the real value determined in patients from the Hospital Clínica Bíblica - Chaverri Fernández, José Miguel (2016)
Objective: to analyze the effect of the modifications in the Cockcroft-Gault equation for creatinine clearance rate determination (CrCl) and its concordance with the real value determined from 24-hours urine collection in a sample of Latin American patients hospitalized in San José de Costa Rica. Method: an observational, retrospective study, with patients submitted to a 24-hour urine collection test, and who met the inclusion criteria. The real and estimated values of creatinine clearance were determined, and their concordance was measured by applying the Intraclass Correlation Coefficient; a descriptive analysis of data was also conducted. Results: there were 507 subjects (61% men); their age was described (ME = 60 years SD = 17 years), as well as their height (ME = 1.66 m SD = 0.09 m), current weight (ME =75 kg SD = 15 kg), body mass index (ME = 27.3 kg/m2 SD = 4.76 kg/m2 ) and endogenous creatinine clearance rates (ME = 69.72 ml/min SD = 33 ml/min). The best concordance with the equation was obtained with current weight values and serum creatinine without rounding. Conclusions: the application of the Cockcroft-Gault equation that matches more closely the real value is the one that uses current weight and does not round creatinine values below 1 mg/dL. It is suggested to conduct a prospective analysis, determining other variables that could affect CrCl real measures, and to replicate this methodology in specific populations. *ME: Mean **SD: Standard Deviation.